Denitrification in the banks of fluctuating rivers: The effects of river stage amplitude, sediment hydraulic conductivity and dispersivity, and ambient groundwater flow. Issue 9 (20th September 2017) - Shuai, Pin; Cardenas, M. Bayani; Knappett, Peter S. K.; Bennett, Philip C.; Neilson, Bethany T.
Abstract: Hyporheic exchange induced by periodic river fluctuations leads to important biogeochemical processes, particularly nitrogen cycling, in riparian zones (RZs) where chemically distinct surface water and groundwater mix. We developed a two‐dimensional coupled flow, reactive transport model to study the role of bank storage induced by river fluctuations on removing river‐borne nitrate. Sensitivity analyses were conducted to quantify the effects of river amplitude, sediment hydraulic conductivity and dispersivity, and ambient groundwater flow on nitrate removal rate. The simulations showed that nitrification occurred in the shallower zone adjacent to the bank where oxic river water and groundwater interacted while denitrification occurred deeper into the aquifer and in the riverbed sediments where oxygen was depleted. River fluctuations greatly increased the amount of nitrate being removed; the nitrate removal rate increased as river amplitude increased. Similarly, increasing hydraulic conductivity increased overall nitrate removal since it expanded the denitrifying zone but decreased efficiency. In contrast, increasing sediment dispersivity increased the removal efficiency of nitrate because it promoted mixing between electron acceptors and donors. The presence and direction of ambient groundwater flow had a significant impact on nitrate removal rate when compared to neutral conditions. A losing river showed a larger nitrate removal rate, whereas a gaining river showed a smaller nitrate removal rate. Our results demonstrated that daily river fluctuations created denitrification hot spots within the RZ that would not otherwise exist under naturally neutral or gaining conditions. Key Points: A two‐dimensional, coupled variably saturated transient flow, and reactive C and N transport model was developed Periodic subdaily river stage fluctuations created localized nitrification and denitrification hot spots within the riparian zone River fluctuation amplitude, sediment hydraulic conductivity, and ambient groundwater flow affect nitrate removal rate